Acronym Formation Study in Waspada Medan Daily Newspaper - Alkaushar Lingga; Edi Yanto ML; Susy Deliani (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study examines the process of making an acronym in the Waspada daily newspaper Medan published on 1, 4 and 6 April 2019. The purpose of this study is to describe the process of forming an acronym in the Waspada Medan daily newspaper published on 1, 4 and 6 April 2019. This research method is a descriptive qualitative method. The research data is sourced from the Waspada Medan daily newspaper on 1, 4, and 6 April 2019. Techniques for collecting data with techniques refer to and are accepted. The results of this study describe the five patterns of the formation of acronyms, namely: (1) Tribal sequencing with tribes, (2) sequencing of tribes with tribes and letters, (3) sequencing of words with tribes and letter, (4) impingement of words with terms and letters, and (5) initial letter. Keywords:acronyms, process, formation, waspada Abstrak Penelitian ini mengkaji tentang proses pembentukan akronim pada surat kabar harian Waspada Medan terbitan tanggal 1, 4 dan 6 April 2019. Tujuan penelitian ini untuk mendeskripsikan proses pembentukan akronim pada surat kabar harian Waspada Medan terbitan tanggal 1, 4 dan 6 April 2019. Metode penelitian ini menggunakan metode kualitatif deskriptif. Data penelitian ini bersumber dari surat kabar harian Waspada Medan tanggal 1, 4, dan 6 April 2019. Teknik pengumpulan data dengan teknik membaca dan mencatat. Hasil penelitian ini mendeskripsikan lima pola proses pembentukan akronim yaitu: (1) Pengekalan suku dengan suku, (2) Pengekalan suku dengan suku dan huruf, (3) Pengekalan kata dengan suku dan huruf, (4) Pelesapan kata dengan suku dan huruf, dan (5) Pengekalan huruf awal. Kata kunci: akronim, proses, pembentukan, waspada